Surface plasmon resonance: advances of label-free approaches in the analysis of biological samples. (December 2014) - Riedel, Tomas; Majek, Pavel; Rodriguez-Emmenegger, Cesar; Brynda, Eduard
Surface plasmon resonance sensors have made vast advancements in the sensing technology and the number of applications achievable. New developments in surface plasmon resonance sensors have gained considerable momentum promoted by the urgent needs of fast, reliable and label-free methods for detection and quantification of analytes in molecular biology, medicine and other life sciences. However, even if enormous improvements in the limits of detections have been achieved, this technology still faces important challenges to be translated to clinical practice or in-field measurements. This paper reviews the important recent advances of this technology for the label-free detection in real biological samples and we discussed the key challenges to be overcome to transit from prototypes to commercial biosensors.